The Effect of Problem Based Learning (PBL) Learning Model on Students' Argumentation Ability on Salt Hydrolysis Material - Prifes, Ramda; Okmarisa, Heppy (Universitas Pendidikan Mandalika, 2024)
The application of problem-based learning model teaches students how to deal with problems and find solutions by expressing opinions and providing logical justification for real problems, so it is expected to improve students' argumentation skills. This study aims to determine the effect of problem-based learning model on students' argumentation skills on salt hydolysis material. This study was carried out in the even semester of the 2022/2023 academic year at MAN 2 Kampar, class XI IPA.Pretest-posttest Non-Equivalent Control Grub Design was the experimental design for this study, which used quasi-experimental methods. The sample consisted of XI IPA1 students as the experimental class and XI IPA2 as the control class. Data collected to measure students argumentation skills through tests and observations and analyzed using t-test and coefficient of determination test in SPSS 24. In the t-test, the Sig (2-tailed) = 0.000 outcome is more modest than 0.05, and that implies H0 is dismissed and Ha is accepted. For the determination test, the value (r2) = 0.284 is obtained, it can be concluded that the problem-based learning model affects students argumentation skills on salt hydrolysis material by 28.4%.